Measurement of solvent properties using kamlet-taft approach for application in synthesis - Islam, Tariqul; Helal Uddin, A.B.M.; Ferdosh, Sahena; Sarker, Md. Zaidul Islam (Malaysian Society of Analytical Sciences, 2022)
Solvents are an unavoidable part of pharmaceutical and chemical manufacturing/synthesis, most of them are toxic or hazardous. The study on toxic solvent replacement is ongoing over the world. Researchers are trying to overcome the hazardous issues that can be possible using the mixture of hydrogen bond donor (HBD) and hydrogen bond acceptor (HBA) solvent as a safe/recommended solvent mixture. This study presents the possibility for the replacement/limitation of dipolar aprotic solvent in drug synthesis using solvent-pair mixture where the Kamlet-Taft (KT) parameter works as a tool to alternate the uses of such types of toxic solvents. It has been simplified here among the many methods and equations of the KT approach. The polarity (π*), basicity (β), and acidity (α) of 10 pure solvents and 16 solvent-pair mixtures were measured spectroscopically, utilizing well-suited dyes or indicators. The highest absorption wavenumber value of indicators in the solution was selected and the simplified KT equations were used to determine the solvent properties (π*, β, α). Solvent mixtures were classified as per the solvent selection guideline of GSK2016 and CHEM21. Four pure solvents (tetrahydrofuran, dimethylformamide, dimethylsulfoxide, and acetone) exhibited low KT acidity, high KT basicity, and high KT polarity. Eight aqueous solvent mixtures (water-acetone, water-ethanol, water-isopropyl alcohol, water-dimethylsulfoxide, water-dimethylformamide, water-tetrahydrofuran), and two non-aqueous solvent mixtures (ethanol-dimethylformamide, ethanol-dimethylsulfoxide) showed low KT acidity and high KT basicity. Solvent classification by composite score showed that four solvent mixtures were as recommended and 5 mixtures were near to recommended solvent among 16 solvent mixtures. KT parameter was a simplified approach to determine which mixture can bind with active pharmaceutical ingredients (API) that is indicated by KT solvatochromic properties and solvent classification.